2017
DOI: 10.3390/nu9050464
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Isomaltulose Together with Green Tea on Glycemic Response and Antioxidant Capacity: A Single-Blind, Crossover Study in Healthy Subjects

Abstract: Isomaltulose, a naturally-occurring isomer of sucrose, is commonly used as an alternative sweetener in foods and beverages. The goal of this study was to determine the effect of isomaltulose together with green tea on postprandial plasma glucose and insulin concentration, as well as antioxidant capacity in healthy subjects. In a randomized, single-blind, crossover study, 15 healthy subjects (eight women and seven men; ages 23.5 ± 0.7 years; with body mass index of 22.6 ± 0.4 kg/m2) consumed five beverages: (1)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 51 publications
0
13
0
1
Order By: Relevance
“…This Special Issue “Effects of Polyphenol-Rich Foods on Human Health” comprises 64 peer-reviewed papers, including 43 original research papers [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 ], one case-report [ 51 ] and 20 literature reviews [ 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 ...…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This Special Issue “Effects of Polyphenol-Rich Foods on Human Health” comprises 64 peer-reviewed papers, including 43 original research papers [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 ], one case-report [ 51 ] and 20 literature reviews [ 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 ...…”
mentioning
confidence: 99%
“…Epidemiological and clinical studies reported the following associations of polyphenols and polyphenol food extracts: silibinin and non-alcoholic fatty liver disease [ 9 , 39 ], resveratrol and hepatic encephalopathy [ 33 ], coffee polyphenols and cardiovascular risk factors [ 34 ], flavonoids and ventilator function [ 20 ], tea and stress and sleep quality (depending on caffeine content) [ 46 ], tea and glycemic response [ 44 ], polyphenols and obesity [ 24 ], phenolic acids and hypertension [ 22 ], healthy diet and neurofibromatosis [ 51 ].…”
mentioning
confidence: 99%
“…Numerous interventional studies have assessed the potential impact of various nutritional compounds added to food [ 17 , 18 ] or beverages [ 19 ] in DFR on the antioxidant potential, or have examined the effect of individual antioxidants (UA, vitamin C, antioxidative enzymes) in plasma or serum, although few have used saliva. However, few studies have evaluated the influence of habitual dietary intake on the antioxidant status, especially its salivary non-urate fraction, which prevents a reliable comparison with the obtained data.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, regular intake of green tea could benefit high-fat diet-induced T2DM [151]. Meanwhile, green tea was found to augment the isomaltulose activity to reduce postprandial glucose and insulin concentration in healthy subjects [152]. Furthermore, supplementation with green tea extract could improve glycemic control and prevent osteoporosis in diabetic patients [153].…”
Section: Anti-diabetic Effect In Humansmentioning
confidence: 99%